The functional characterisation of murine CLEC-2 and analysis of the expression of its ligand, podoplanin, on macrophages - Kerrigan, Ann (Department of Clinical Laboratory Sciences, 2014)
Includes abstract. Includes bibliographical references (p. 109-125).